2010
DOI: 10.1159/000316263
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Health Characteristics of Urban South Korean Women

Abstract: Aims: To characterize the reproductive health of urban South Korean women of reproductive age. Methods: A cross-sectional online survey on menstrual patterns, sexual behavior, utilization of contraception, and perception of gynecological diseases was administered to 500 women from 15 to 39 years of age in five major cities of South Korea. Results: Among the respondents, 76.8 and 25% experienced dysmenorrhea and abnormal uterine bleeding, respectively. Two-thirds of the respondents with dysmenorrhea used analge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…Fibroids, occurring in almost a quarter of women in reproductive age, become more common with advancing age [2]. They are also more commonly seen in nulliparity; the risk decreases with the number of successful pregnancies and becomes very low in women with several children [3].…”
Section: Introductionmentioning
confidence: 99%
“…Fibroids, occurring in almost a quarter of women in reproductive age, become more common with advancing age [2]. They are also more commonly seen in nulliparity; the risk decreases with the number of successful pregnancies and becomes very low in women with several children [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, while experience with oral contraceptives was common in the US, with a similar rate of use as withdrawal, the rate of use appeared to be apparently lower in Korea (15.0% vs. 9.2% in 2015). This difference may be a result of the negative attitudes among Korean women towards the use of hormonal contraceptives related to concerns about weight gain, permanent infertility and being considered promiscuous [12]. The accessibility of hormonal contraception may also be lower for Korean female adolescents because sexual activity in adolescents is frowned upon, and because some types require prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there exists poor understanding of and a cultural prejudice against OCs in Korea. The frequency of OC use is lower in Korea than in Western countries [18]. Some investigators have demonstrated that Asian women have a cultural bias against OC use.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the result that Korea OC nonusers are comprised of more women who fear the side effects of OCs, it is inferred that Korean OC nonusers are more likely to be health conscious than OC users. In particular, 62.2% of Korean women reported incorrect information about the benefits and risks of OCs [18]. Incorrect information puts a barrier to women who desire contraception by causing an overestimation of the risks of OCs.…”
Section: Discussionmentioning
confidence: 99%